Temporal studies into attachment, VE-cadherin perturbation, and paracellular migration of human umbilical mesenchymal stem cells across umbilical vein endothelial monolayers - Ebrahim, Neven A.; Leach, Lopa (Mary Ann Liebert, 2015)
Mesenchymal stem cells from Wharton’s jelly of human umbilical cords (WJ-MSC) are a valuable alternate source of stem cells. Their role in situ and whether they can interact and cross intact endothelial monolayers requires elucidation. The aim of this study was to investigate the dynamic interactions between WJ-MSC and human umbilical vein endothelial cells (HUVEC), including attachment, transit times, extravasation pathway, and the effects of WJ-MSC on junctional vascular endothelial (VE)-cadherin. HUVEC were grown to near confluence in endothelial media and to full confluence in mixed media before the addition of PKH26-labelled WJ-MSC. Time lapse fluorescence microscopy showed stem cells undergoing membrane blebbing followed by amoeboid movement on HUVEC monolayers before rounding up and changing shape toward the spindleshaped morphology during/after transmigration to subendothelial positions. Cells demonstrated a time lag of 60 min before paracellular extravasation, confirmed by confocal microscopy. Forty-six percent of attached cells crossed in the first 2 h. By 16 h, a majority of cells had transmigrated with > 96% of cells crossing by 22 h. There were concomitant changes in endothelial junctional VE-cadherin with statistically significant increases in discontinuous staining at 2 h, return to control values at 16 h, even as from 22 h onward HUVEC displayed increased percentage of junctions with continuous staining and upregulation of protein. Our data suggests that WJ-MSC crosses the endothelial barrier through the paracellular pathway and can influence junctional organization of HUVEC with discreet perturbation of VE-cadherin preceding transmigration followed by upregulation once the adluminal side is reached. The latter may reflect a perivascular support function of WJ-MSC in the umbilical cord.